The impact of redistributive policies on inequality in OECD countries - Philipp Doerrenberg; Andreas Peichl (Institute for the Study of Labor (IZA), 2012)
Recent discussions about rising inequality in industrialized countries have triggered calls for more government intervention and redistribution. Due to obvious behavioral effects caused by redistribution, it is however not clear whether redistributional policies are indeed able to combat inequality. This paper contributes to this relevant research question by using different contextual country-level data sources to study inequality trends in OECD countries since the 1980s. We first investigate the development of inequality over time before analyzing the question of whether governments can effectively reduce inequality. Different identification strategies, using fixed effects and instrumental variables models, provide some evidence that governments are capable of reducing income inequality despite countervailing behavioral adjustments. The effect is stronger for social expenditure policies than for progressive taxation, which seems to trigger more inequality increasing indirect behavioral effects. Our results also suggest that the use of secondary inequality data should be handled with caution.
urn:nbn:de:101:1-201208096160
Keywords: D31; D60; H20; 330; inequality; redistribution; social expenditure; progressive taxation; Einkommensumverteilung; Wirkungsanalyse; Soziale Ungleichheit; Öffentliche Sozialausgaben; Steuerprogression; OECD-Staaten